Ekranisasi Novel A+ menjadi Serial Web A+: Kajian Penciutan, Penambahan, dan Perubahan Bervariasi - Julianda, Fitri; Amalia Nadina, Diya; Hidayati, Yushfi Shabrina; Yanti, Nur Helda (UPA Bahasa Universitas Tidar And HISKI Kedu, 2025)
This study aims to explain how the novel A+ by Ananda Putri was transformed into the web series A+ directed by Fajar Bustomi. The focus of this study is to analyze various forms of simplification, additions, and changes that occurred in the elements of the plot, setting, and characters and character depictions based on the theory of ecranization by Pamusuk Eneste. The method used in this study is a qualitative method with a descriptive-analytical approach and a comparative literary research type. The data sources consist of the novel and the web series A+ available for viewing on Prime Video. The results of this study indicate that the ecranization process resulted in simplifications in several elements of the plot, setting, and characters that are not directly related to the main conflict. In addition, there are also additions of elements of the plot, setting, and characters to strengthen the themes of education and mental health among students. Thus, it can be concluded that the transformation from the novel A+ to the web series A+ still maintains the core of the story, despite undergoing various changes in its structure.